1983
DOI: 10.1002/aja.1001670103
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the arterial and lacunary systems of the ventricular myocardium of elasmobranch and teleost fishes

Abstract: The typical fish heart has a spongy trabeculated ventricular myocardium (spongiosa) supplied by the venous blood of the intertrabecular spaces (lacunae); hence it is called a "venous heart." However, in some fishes a more complex ventricular muscle is found (mixed type), in which the spongiosa is covered by an outer layer of densely arranged myocardial bundles (compacta). The compacta receives oxygenated blood from the coronary vessels. The objective of this study was to investigate relations between myoarchit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(81 citation statements)
references
References 24 publications
2
76
1
Order By: Relevance
“…These data suggest that the relationship between hypoxic adaptation and preconditioning in the trout heart resembles that of the neonatal/immature, not adult, mammalian heart. It is tempting to associate myocardial preconditioning with myocardium that is supplied with blood from the coronary circulation because the rat heart becomes increasingly dependent on its coronary circulation as it ages, and rainbow trout possess a coronary circulation (Tota et al, 1983) that supplies blood to the compact myocardium, which comprises the outer one-third of the heart (Fig.·5). However, the hypoxiasensitive heart of Atlantic cod Gadus morhua, which lacks a coronary circulation and is composed entirely of spongy myocardium, can be preconditioned (A. G. Genge and A. K. Gamperl,unpublished;Fig.·6) in much the same way as rainbow trout (Gamperl et al, 2001).…”
Section: Hypoxic Acclimationmentioning
confidence: 99%
“…These data suggest that the relationship between hypoxic adaptation and preconditioning in the trout heart resembles that of the neonatal/immature, not adult, mammalian heart. It is tempting to associate myocardial preconditioning with myocardium that is supplied with blood from the coronary circulation because the rat heart becomes increasingly dependent on its coronary circulation as it ages, and rainbow trout possess a coronary circulation (Tota et al, 1983) that supplies blood to the compact myocardium, which comprises the outer one-third of the heart (Fig.·5). However, the hypoxiasensitive heart of Atlantic cod Gadus morhua, which lacks a coronary circulation and is composed entirely of spongy myocardium, can be preconditioned (A. G. Genge and A. K. Gamperl,unpublished;Fig.·6) in much the same way as rainbow trout (Gamperl et al, 2001).…”
Section: Hypoxic Acclimationmentioning
confidence: 99%
“…It is interesting to note we have previously documented that in the eel A. anguilla heart, used as a paradigm of a highly trabeculate and endoluminally supplied cardiac design (Tota et al 1983), a basal release of endogenous NO increases the sensitivity of the Frank-Starling response (Imbrogno et al 2001). These studies using avascular working heart preparations, including the amphibian heart (Sys et al 1997), showed that this effect cannot be attributed to a rise in coronary flow or to factors released from vascular tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, if an increase in myocardial mass is desired, the heart muscle is organized into a spongy meshwork of trabeculae. The same arrangement of myocardium can be found even in some lower vertebrates, typically cold-blooded, relatively sedentary animals with low blood pressure, notably some fish (Ostadal and Schiebler, 1971;Tota et al, 1983) and amphibian species such as Xenopus, that has a coronaryless ventricle, although with rudimentary coronary vessels supplying the atrioventricular canal and the arterial pole .…”
mentioning
confidence: 67%